LTe2 induces cell apoptosis in multiple myeloma by suppressing AKT phosphorylation at Thr308 and Ser473 - Zhang, Yuanjiao; Qian, Jiacheng; Jiang, Mingmei; Yang, Shu; Zhou, Lianxin; Zhang, Qin; Lin, Liping; Yang, Ye (Frontiers in Oncology, 2023)
Multiple myeloma (MM) is a highly heterogeneous hematological malignancy originating from B lymphocytes, with a high recurrence rate primarily due to drug resistance. 2-((1H-indol-3-yl)methyl)-3-((3-((1H-indol-3-yl)methyl)-1H-indol-2-yl)methyl)-1H-indole (LTe2), a tetrameric indole oligomer, possesses a wide range of anticancer activities through various mechanisms. Here, we aim to explore the anti-tumor efficiency and potential downstream targets of LTe2 in MM. Its bioactivity was assessed by employing MTT assays, flow cytometry, and the 5TMM3VT mouse model. Additionally, transcriptomic RNA-seq analysis and molecular dynamics (MD) experiments were conducted to elucidate the mechanism underlying LTe2 induced MM cell apoptosis. The results demonstrated that LTe2 significantly inhibited MM cell proliferation both in vitro and in vivo, and revealed that LTe2 exerts its effect by inhibiting the phosphorylation of AKT at the Thr308 and Ser473 sites. In summary, our findings highlight the potential of LTe2 as a novel candidate drug for MM treatment and provided a solid foundation for future clinical trials involving LTe2.